2010
DOI: 10.1007/s00221-010-2187-5
|View full text |Cite|
|
Sign up to set email alerts
|

Robot-assisted modifications of gait in healthy individuals

Abstract: This study investigated whether short-term modifications of gait could be induced in healthy adults and whether a combination of kinetic (a compliant force resisting deviation of the foot from the prescribed footpath) and visual guidance was superior to either kinetic guidance or visual guidance alone in producing this modification. Thirty-nine healthy adults, 20-33 years old, were randomly assigned to the three groups receiving six 10-min blocks of treadmill training requiring them to modify their footpath to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 52 publications
4
43
1
Order By: Relevance
“…In [44], the authors studied the short-term modifications of gait induced by six consecutive 10-minute-long training sessions with Active Leg EXoskeleton (ALEX) [45], [46]. The results supported the hypothesis that combined kinetic and visual guidance might be more effective than kinetic or visual guidance alone in inducing short-term motor adaptations.…”
mentioning
confidence: 58%
“…In [44], the authors studied the short-term modifications of gait induced by six consecutive 10-minute-long training sessions with Active Leg EXoskeleton (ALEX) [45], [46]. The results supported the hypothesis that combined kinetic and visual guidance might be more effective than kinetic or visual guidance alone in inducing short-term motor adaptations.…”
mentioning
confidence: 58%
“…In the context of neural rehabilitation, these NRs are an attractive but yet not fully explored technique to reinforce the effect of the basis for rehabilitation: neural feedback. When acting actively through its actuators, and demanding an active intervention from the patient, muscle coordination patterns might be restored or more accurately and effectively be substituted through NRs [55]. At this time, with regard to stroke rehabilitation therapy, interventions driven by such NRs have demonstrated to be at least as effective as conventional therapy [16] but there is not yet a consensus with respect to effectiveness [17] at chronic or acute stages after stroke.…”
Section: Nr Exoskeletons In Physical Therapymentioning
confidence: 98%
“…Other efforts on patient-cooperativeness have been focused on advancing the classical impedance control in order to overcome the disadvantage of imposing timing of movements to the limbs of the patient. The idea of a virtual tunnel [7] to allow some range of free movement was introduced with the MIT-Manus [61] and tested with stroke patients in the lower limb exoskeleton ALEX [55]. Likewise, an algorithm was proposed for the Lokomat exoskeleton that allows users to move actively along a spatial path of a defined walking pattern, which is referred to as path control.…”
Section: Motor Learning Principles and Robotic Control Approachesmentioning
confidence: 99%
“…Moreover, a recent study showed that a robot-assisted training program combining a force-field constraint with real-time visual feedback could facilitate an adaptation of healthy people's locomotion patterns [16]. Adding somatosensory inputs using a force-field to realtime visual feedback training also appears to enhance the motor adaptation or learning in individuals with stroke [11].…”
Section: B Robot-assisted Balance Trainingmentioning
confidence: 99%